Self-reported empathy among nursing students of school of health sciences, Universiti Sains Malaysia - Sani, Fatinnur Badrina Ahmad (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2022)
Empathy has a significant impact on the relationship between nurses and patients, and on the quality of care that they provide. Since the time when the concept of empathy was first introduced into the field of nursing science, it has come to be acknowledged as an essential component of efficient nursing care as well as in nursing education. This study aimed to assess the level of empathy among nursing students of School of Health Sciences, Universiti Sains Malaysia. Besides that, this study also investigates the association between socio-demographic data with the level of empathy among nursing students of School of Health Sciences, Universiti Sains Malaysia. Data was collected through a set of questionnaires adapted by Spreng et al. (2009) that was distributed through an online platform, from March 2022 to May 2022. A total of 187 nursing students aged between 18 to 29 years old from diploma and degree programme were involved in this study. The findings revealed that majority of nursing students in USM (n = 111, 59.4%) have a high level of empathy. Two socio-demographic data which are gender (p = 0.001) and programme of study (p = 0.016) have statistically significant difference with level of empathy. In conclusion, even though most of the nursing students in USM have high level of empathy, the findings also show quite a few numbers of students with low level of empathy, which means there are still students with lack of empathy. Hence, a further ability of education needs to be considered to improve empathic response.